Anti-integral extensions R[α]/R - Baba, Kiyoshi; Yoshida, Ken-Ichi (Tamkang Journal of Mathematics, 2004)
Let R be an integral domain and α an anti-integral element of degree d over R . In the paper [3] we give a condition for α^2-a to be a unit of R[α] . In this paper we will generalize the result to an arbitrary positive integer n and give a condition, in terms of the ideal I_[α]^nD([n]a) of R , for α^n-a to be a unit of R[α] .